2021
DOI: 10.12998/wjcc.v9.i28.8388
|View full text |Cite
|
Sign up to set email alerts
|

Validated tool for early prediction of intensive care unit admission in COVID-19 patients

Abstract: BACKGROUND The novel coronavirus disease 2019 (COVID-19) pandemic is a global threat caused by the severe acute respiratory syndrome coronavirus-2. AIM To develop and validate a risk stratification tool for the early prediction of intensive care unit (ICU) admission among COVID-19 patients at hospital admission. METHODS The training cohort included COVID-19 patients admitted to the Wuhan Third Hospital. We selected 13 of 65 baseline laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…After full-text assessment, 343 studies were excluded due to inappropriate study design, no relevant outcome, unavailable full-text, pre-prints, irrelevance to research question, model performance not reported, or studies including human participants under 18 years. After examining full-texts, we identified 314 eligible articles, of which 152 (48.4%) presented mortality as the outcome [4,5,, 66 (21.0%) concentrated on severity and/or critical illness [2,, 35 (11.1%) presented ICU admission and mortality combined [7,, 17 (5.4%) assessed ICU admission only [225,[260][261][262][263][264][265][266][267][268][269][270][271][272][273][274][275], 6 (1.9%) looked at mechanical ventilation only [276][277][278][279][280][281] and 38 (12.1%) assessed multiple combined outcomes [195,. We present the results in the PRISMA flow chart Fig.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…After full-text assessment, 343 studies were excluded due to inappropriate study design, no relevant outcome, unavailable full-text, pre-prints, irrelevance to research question, model performance not reported, or studies including human participants under 18 years. After examining full-texts, we identified 314 eligible articles, of which 152 (48.4%) presented mortality as the outcome [4,5,, 66 (21.0%) concentrated on severity and/or critical illness [2,, 35 (11.1%) presented ICU admission and mortality combined [7,, 17 (5.4%) assessed ICU admission only [225,[260][261][262][263][264][265][266][267][268][269][270][271][272][273][274][275], 6 (1.9%) looked at mechanical ventilation only [276][277][278][279][280][281] and 38 (12.1%) assessed multiple combined outcomes [195,. We present the results in the PRISMA flow chart Fig.…”
Section: Literature Searchmentioning
confidence: 99%
“…In total, there were only 17 (5.4%) studies which reported ICU admission as their outcome [225,[260][261][262][263][264][265][266][267][268][269][270][271][272][273][274][275]. Sample size in these studies varied from 67 to 4663 participants with a mean age ranging from 40 to 71.4 years and percentage male between 39.5% and 75.8%.…”
Section: Models Predicting Icu Admission Onlymentioning
confidence: 99%